Adaptive immunity suppresses formation and progression of diethylnitrosamine-induced liver cancer. Issue 12 (20th January 2012) - Schneider, Carlo; Teufel, Andreas; Yevsa, Tetyana; Staib, Frank; Hohmeyer, Anja; Walenda, Gudrun; Zimmermann, Henning W; Vucur, Mihael; Huss, Sebastian; Gassler, Nikolaus; Wasmuth, Hermann E; Lira, Sergio A; et al.
Abstract : Background: Hepatocellular carcinoma (HCC) is a typical inflammation-associated cancer, but may also provoke antitumour immune responses whose significance and underlying mechanisms are incompletely understood. Objective: To characterise immune responses in the diethylnitrosamine (DEN)-liver cancer mouse model. Design: Tumour development and immune cell functions upon DEN treatment were compared between C57BL/6 wild-type (WT), chemokine scavenging receptor D6-deficient, B cell- (Igh6), CD4 T cell- (MHC-II) and T-/B cell-deficient (Rag1) mice. Relevance for human HCC was tested by comparing gene array results from 139 HCC tissues. Results: The induction of premalignant lesions after 24 weeks and of HCC-like tumours after 42 weeks by DEN in mice was accompanied by significant leucocyte infiltration in the liver and upregulation of distinct intrahepatic chemokines (CCL2, CCL5, CXCL9). Macrophages and CD8 (cytotoxic) T cells were most prominently enriched in tumour-bearing livers, similar to samples from human HCC. Myeloid-derived suppressor cells (MDSC) increased in extrahepatic compartments of DEN-treated mice (bone marrow, spleen). The contribution of immune cell subsets for DEN-induced hepatocarcinogenesis was functionally dissected. In D6 −/− mice, which lack the chemokine scavenging receptor D6, hepatic macrophage infiltration was significantly increased, but tumour formation and progression did not differ from that of WT mice. In contrast, progression of hepatic tumours (numbers, diameters, tumour load) was strikingly enhanced in T-/B cell-deficient Rag1 −/− mice upon DEN treatment. When mice deficient for B cells (Igh6 −/−, μMT) or major histocompatibility complex II were used, the data indicated that T cells prevent initial tumour formation, while B cells critically limit growth of established tumours. Accordingly, in tumour-bearing mice antibody production against liver-related model antigen was enhanced, indicating tumour-associated B cell activation. In agreement, T and B cell pathways were differentially regulated in gene array analyses from 139 human HCC tissues and significantly associated with patients' survival. Conclusions: Distinct axes of the adaptive immune system, which are also prognostic in human HCC, actively suppress DEN-induced hepatocarcinogenesis by controlling tumour formation and progression.